2010
DOI: 10.1016/j.injury.2010.07.326
|View full text |Cite
|
Sign up to set email alerts
|

Audit: initial assessment and management of fracture neck of femur patients in the emergency department and the “Fast Track” system

Abstract: Patients were split into further subgroups; those having early surgery <48 h (51%) vs. late surgery >48 h (49%), those who were treated for an extracapsular fracture vs. those treated for an intracapsular fracture, then divided again into early surgery vs. late surgery. We found the larger Hb drop (mean 3.2 g/dL) in the early surgery group vs. 2.35 g/dL in the late group with no significant difference in blood loss between groups (p = 0.074). Average length of stay was 21.13 (range 5-58) in the early and 22.93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study conducted by Chamisa et al, 10 it is documented that 61% of the files had examination details . In another study done by Osei-Kufuor et al, 11 it was revealed that 61% had no detailed examination reports .…”
Section: Resultsmentioning
confidence: 91%
“…In a study conducted by Chamisa et al, 10 it is documented that 61% of the files had examination details . In another study done by Osei-Kufuor et al, 11 it was revealed that 61% had no detailed examination reports .…”
Section: Resultsmentioning
confidence: 91%